Problem-based learning module of organic insecticide for the aborigine students in Malaysia - Low Suan Ee; Liang Yun Chinn; Zhao Zhifeng; Nor Hasniza Ibrahim; Johari Surif; Nabilah Abdullah; Muhamad Nur Fariduddin (International Journal of Evaluation and Research in Education (IJERE), 2023)
Problem-based learning (PBL) is a teaching model that uses real-world problems to lead students toward the learning objective of a course. It has been widely adopted in Malaysian education. However, PBL module for aboriginal people is scarce. This study aimed to provide suitable PBL activities in learning environmental problems by developing a PBL teaching module for the aborigine community and accessing its suitability. In this study, data was collected through an online validation form that was given to four validators, all of them have science or chemistry education backgrounds. The online questionnaires collected were further analyzed to investigate their responses to the module. The result has shown positive feedback (95.83%) as the responses are very encouraging. All respondents give approbation to the objectives of the module which are clearly stated and are parallel with the content. Many of them also strongly agree that the PBL model and the language used are suitable in this module. There is no doubt that PBL is a valuable tool to teach chemistry to improve students’ critical thinking and problem-solving skills effectively.